KARAKTERISTIK DAN DISTRIBUSI REKAHAN ALAMI, STUDI ANALOG PADA SINGKAPAN BATUAN DASAR CEKUNGAN OMBILIN, SUMATRA BARAT - YOAN TORENO , EKO
Naturally fractured basement is an important element of hydrocarbon reservoirs that have been produced, but it is still difficult to describe the characteristics bellow the surface, although it can be studied using image log data, core, and geophysics, but not many wells penetrated it and equipped with the log image. One of the best method to predict and provide an understanding of the characteristics of naturally fractured basement at subsurface is a measurement with scanline method and windows scan with observations on basement outcrops.